(untitled) (Applied Biological Research, 2014)
The present study was aimed to evaluate the impact of ginger, cinnamon bark, chicory and stevia extract-supplemented feeds on serum clinical biochemistry and production performance in Jabalpur colour birds. Fifty four birds of 32 weeks age were randomly divided into 9 groups of 6 birds each. Control group was fed normal basal feed whereas rest groups were fed on feeds supplemented with alcoholic extracts of various herbs separately at 2 levels each [ginger, cinnamon and stevia extract mixed with feed @ 2.5 and 5.0 g kg-1feed and chicory extract @ 1.25 and 2.5 g kg-1 feed]. Blood samples, collected on 0, 14, 28, 42 and 56th day of treatment, revealed a non-significant decrease in lipid peroxidase and non-significant increase in superoxide dismutase activity in birds of treatment groups. Reduced glutathione showed significant increase in all the treatment groups with higher value in birds fed with chicory (2.5 g kg-1) and cinnamon (5 g kg-1) supplemented feed, respectively. Glucose-6-phosphate dehydrogenase showed significant increase from days 0 to 56 in all the treatment groups. Alanine aminotransferase and aspartate aminotrans ferase showed a decreasing trend and significant lowering effect was noticed in birds fed with chicory and ginger. The serum creatinine showed significantly low value in chicory (2.5 g kg-1) fed birds. No significant variation was observed in blood urea nitrogen. Increase in egg weight was significant higher in treatment groups with highest increase in ginger @ 5 g kg-1 fed birds. The supplementation of herbal drugs increased body weight significantly as the interval of time increased up to 56th days with highest weight in birds fed with chicory @ 2.5 g kg-1feed.